Creating an accessible and effective pathway for regional and isolated Aboriginal and Torres Strait Islander people to tertiary study using block-release study mode : final report 2014. - Turnbull, Mattie (Australia. Office for Learning and Teaching, 2014)
This report discusses the findings of a project that set out to address the current low retention rates among Indigenous Australian students from regional and isolated areas undertaking degree courses offered through block-release study mode by the Centre for Aboriginal Studies at Curtin University, Western Australia. It compares these retention rates to those of students undertaking other degree courses offered by the University, and notes that current drop-out rates for these students are up to 60 per cent, compared with 20 per cent for the overall student population of Curtin University. The project endeavoured to establish the feasibility of developing a bridging course style program for these students, in the form of a block-release study mode pre-tertiary academic pathway program. This pathway program would be designed to attract and retain regional and isolated Indigenous Australians by ensuring that these students are equipped with the skills required for the successful completion of their degree course. The project found that existing pathway programs do not effectively meet these needs, and suggested that a pathway program should be offered which focuses on academic writing and culture (in particular, in-depth research and referencing skills), written and oral communication skills, mathematics, and online learning methodologies, through hands on' experience during block release. It anticipates that such a pathway program would stem the current drop-out rate. [Executive summary, ed]